Analisis Kompensasi Sebagai Pendorong Kinerja Karyawan Pada Yayasan Al – Azka Kamila Indonesia Cisauk Kabupaten Tangerang - Allen Nadzirin Isron; Siska Yunanti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. This study aims to analyze the implementation of compensation and its role in encouraging employee performance at Al–Azka Kamila Indonesia Foundation, Cisauk, Tangerang Regency. Compensation is an important aspect of human resource management because it influences employee motivation, loyalty, and performance in carrying out their duties and responsibilities.This research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The informants consisted of five employees, including two administrative staff, two teachers and the head of the foundation., who were selected based on their direct involvement in the foundation’s operational activities. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured using source triangulation.The results indicate that the implementation of compensation at Al–Azka Kamila Indonesia Foundation has not been fully optimal. In terms of financial compensation, some employees receive basic salaries below the Regional Minimum Wage standard, although payments are made regularly and on time. In addition, non-financial compensation such as allowances, incentives, and a supportive work environment contributes to employee comfort and work motivation. However, several obstacles remain, particularly in terms of work efficiency, timeliness, and innovation. Therefore, compensation plays an important role as a driving factor for employee performance, but improvements and adjustments are needed to achieve fairness and sustainability in enhancing overall employee performance.